Perbandingan Sistem Pendidikan Indonesia dan Jepang - Dian Montanesa; Firman Firman (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
The educational system between Indonesia and Japan is different. The educational system in Indonesia and in Japan has its own advantages and disadvantages. Currently the education system in Indonesia needs more attention because it was ranked 72 out of 77 countries. In Indonesia, many educational science experts have been born who can bring the educational system in Indonesia to a better direction. One of the ways to bring Indonesia's educational system to a better direction is to compare it to a country with a good education system such as Japan. In Japan, from the age of 0-3, children are more instilled in moral values, manners, discipline and politeness. When children in Japan have entered grade 4 elementary school, then the children take the test which is not too burdensome for students at school. Indonesia can learn a lot with the educational system in Japan.